Sleep quality determinants among nursing students - Silva, Madalena (2016)
Higher education has influenced students’ concepts of sleeping time leading to a deficit of sleep quality. Sleep disorders constitute one of the most pertinent health problems in western society. Identify the factors that influence the sleep quality in nursing students; Identify which social demographic and academic variants interfere with sleep quality; Analyze the influence of variables of psychological context and investigate the relationship between the daytime somnolence with the sleep quality in nursing students. Analytic, descriptive and correlational study in a non-probabilistic convenience sample of 403 nursing students. We applied a Sociodemographic and Academic characterization survey, Epworth Sleepiness Scale, Positive and Negative Affect Scale, Eysenck Personality Inventory, Anxiety scale, Stress and depression and Pittsburgh h Sleep Quality Index. The students’ average age is 23.61 years. Women (86.0%) attending the fourth year (27.4%) reveal less sleep quality (63.2%) and more daytime somnolence (24.3%). First year students aged 20 years residing alone in rural areas present higher levels of anxiety, are less extroverted and more neurotic, reveal less sleep quality. Sleep disorders constitute a public health problem that requires intervention and adopting educational measures and promoting health awareness raising in educational institutions in order to improve student action in building up of their own sleep quality.